THE IMPACT OF GOVERNMENT PROJECTS IN AGRICULTURE SECTOR FOR ECONOMIC DEVELOPMENT (INPUT-OUTPUT MODEL) : THE CASE OF INDONESIA - , Siti Fajriyah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine the impact of government projects in the agriculture sector for economic development in Indonesia in the terms of induced output, induced income and induced employment by using the input output model. It will focus on the three main agricultural commodities namely rice, maize, and soybean. The government projects have the purpose of improving household income and achieving self-sufficiency programs in rice, maize and soybean production. There are three types of subsidy in this study called seed subsidy, fertilizers and pesticides subsidy and machines and tools subsidy. The first objective is to examine the impacts from government projects in the form of the agriculture inputs subsidy. By using Input Output Analysis, this part reveals that the seed subsidy gives the highest induced output, induced income and induced employment among other types of subsidy. Seed subsidy seems have the best impact for stimulating economic activities, it especially stimulates agriculture sectors and agriculture-related industries and service sectors and contributes more to improvement of agriculture labor income. Because of the difference in impact of subsidy types and limitation of national budget, in order to optimize the effect of government expenditure on agriculture products self-sufficiency program, it is important to find what kind of optimal expenditure will support this national purpose best. In the second part, this study reveals the optimal solutions of the amount of seed subsidy and fertilizers and pesticides subsidy because these subsidies are granted in order to give full back up for certain production expectation. By using Linear Programming, it can be found that the optimal budget for seed subsidy and fertilizers and pesticides subsidy are less than the original government budget. The optimized results indicate that the government can save the expenditure while pursuing the self-sufficiency program. It gives a better decision in distributing qualified agriculture inputs subsidy by considering the demand of each sub-type of subsidy. In order to understand the impacts of the optimized budget of each type of subsidy in the economy, Input Output analysis will be used in the third part of this subsidy.Examining the impacts of optimal amount of government expenditure is important in order to elaborate how every type of subsidy influence induced output, induced income and induced employment in economy. The change of the composition of final demand caused the change of induced effects and also the sectors generated by it. It might depend on the inter linkages among sectors in the economic structure. The higher the sector role in economic activities related to final demand, the better the sector share. The type of subsidy gives a characteristic influence to sectors which generated by. The results show that, at the optimal government expenditure, seed subsidy has the highest output ratio, income ratio and employment ratio.